Patterns in Religious thought in early south India: A study of Classical Tamil Texts - Subbiah, Ganapathy (My University, 1988)
This thesis is an analytic study of specific patterns of religious thought in early south India as found in the earliest extant literary texts in Tamil, one of the classical languages of India and one of the oldest living languages of the world. commonly known in the Tamil tradition as the cankaa literature, this corpus of poetry is generally assigned to the early centuries of the Comaon Era, and is thought of as constituting the classical heritage of Taail culture. There has not been a major attempt to investigate the importance of this reaarkable body of literature to the development of religious thought in south India, a region which is widely acknowledged as the birthplace of a number of religious movements including the great devotional govement of the early medieval ties, called the bhaktl religion. The reluctance on the part of historians of Indian religious thought to take up the study of classical Tamil texts was partly due to a perception that the classical Tamil texts were essentially 'secular', and, therefore, of not much interest to a historian of religious thought. I had, therefore, to begin the thesis with a historiographical critique showing how limited and limiting that perception was and suggesting that, whatever unique features that classical Tamil texts may have, they are not unyielding to the queries of a student of religion. In addition to other types of poems, there are a few explicitly religious poems which are regarded by tradition as part of the classical corpus. Taking my initial cues from those poems, I have isolated three central themes in the literature, namely space, hero, and gift around which the religious thought of the culture can be discerned. By a careful and selective analysis of the so-called 'secular' poems in the corpus, and through an analysis of sections of the major grammatical treatise of the classical period, have shown that the thought underlying these three themes was integral to classical Tamil culture. The thesis has in the end a dual purpose. Its stated purpose is to assess the importance of the period of the classical Tamil texts in religious history, but it also indirectly demonstrates the need for a fresh approach to the study of early Tamil literature.
Keywords: Tamil texts; south india